2012
DOI: 10.1007/s00405-012-2194-1
|View full text |Cite
|
Sign up to set email alerts
|

The effects of levobupivacaine infiltration on post-tonsillectomy pain relief in adults: a single-blinded, randomized, and controlled clinical study

Abstract: The aim of this prospective single-blinded and controlled study is to evaluate the efficacy of levobupivacaine infiltration on post-tonsillectomy pain relief in adults. The study was conducted with 40 adult patients who underwent tonsillectomy. These patients were randomized in either study group (SG) who received levobupivacaine infiltration to peritonsillary fossae prior to surgery or control group (CG) with no medication. After surgery, all the patients were queried for pain scores by visual analog scale. I… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
11
0

Year Published

2014
2014
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(11 citation statements)
references
References 21 publications
0
11
0
Order By: Relevance
“…However, the analgesic benefit reported in some studies was minor and limited to the very early postoperative period [20, 21]. No evidence favouring one local anaesthetic agent over another was found.…”
Section: Paracetamolmentioning
confidence: 99%
“…However, the analgesic benefit reported in some studies was minor and limited to the very early postoperative period [20, 21]. No evidence favouring one local anaesthetic agent over another was found.…”
Section: Paracetamolmentioning
confidence: 99%
“…Dhiwakar also reported that antibiotics reduced the proportion of fever among post-tonsillectomy patients (P 0.002) [10]. Telian though didn't measure febrile episodes as an outcome parameter in their study; they found antibiotic usage associated with decreased halitosis in the treatment group compared to placebo [11] Halitosis can be regarded as an indirect evidence of infection. Grandis et al also found patients on antibiotics had less mouth odour compared to those on placebo reflecting the role of antibiotics in preventing infection [12].…”
Section: Fevermentioning
confidence: 99%
“…Recent studies, such as those by Erdogan et al in 2014 and Kaspoglu et al in 2013, demonstrated statistically significant reductions in pain scores among adult tonsillectomy patients treated with bupivacaine in comparison with placebo. 16,17 Alternatively, in 1993 Schoem et al executed a prospective randomized double-blind study with plain bupivacaine after adult tonsillectomy, looking at pain intensity scores, medication usage, and oral intake. 18 Their study showed no significant difference between the group receiving the bupivacaine injection and the group receiving a saline injection, and this has been seen in others' studies as well.…”
Section: Mean Liquid Oral Intakementioning
confidence: 99%